2016
DOI: 10.1128/jvi.01279-16
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Infection Triggers Epithelial HMGB1 Release as a Damage-Associated Molecular Pattern Promoting a Monocytic Inflammatory Response

Abstract: Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract infections in infant and elderly populations worldwide. Currently, there is no efficacious vaccine or therapy available for RSV infection. The molecular mechanisms underlying RSV-induced acute airway disease and associated long-term consequences remain largely unknown; however, experimental evidence suggests that the lung inflammatory response plays a fundamental role in the outcome of RSV infection. High-mobility group box 1 (HM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 70 publications
2
105
0
Order By: Relevance
“…In natural infections, RSV replicates to high levels in airway epithelial cells of the nasal, tracheal, and lower airways, including type I and II alveolar epithelial cells [2,3]. It is well established that RSV-infected epithelial cells rapidly secrete cytokines [36], interferons [21], exosomes [37], and damage-associated patterns [38]. Many of these epithelial specific cytokines, such as type III interferons (IFNs), IL-33, MCP, and MIP1α, can be detected in the airway fluids of naturally infected children with LRTI and experimentally challenged adults [6,9,39,40].…”
Section: The Role Of the Airway Epithelium In Innate Responses To Rsvmentioning
confidence: 99%
See 1 more Smart Citation
“…In natural infections, RSV replicates to high levels in airway epithelial cells of the nasal, tracheal, and lower airways, including type I and II alveolar epithelial cells [2,3]. It is well established that RSV-infected epithelial cells rapidly secrete cytokines [36], interferons [21], exosomes [37], and damage-associated patterns [38]. Many of these epithelial specific cytokines, such as type III interferons (IFNs), IL-33, MCP, and MIP1α, can be detected in the airway fluids of naturally infected children with LRTI and experimentally challenged adults [6,9,39,40].…”
Section: The Role Of the Airway Epithelium In Innate Responses To Rsvmentioning
confidence: 99%
“…Interestingly, many of these secreted proteins do not contain classic signal peptides, suggesting novel and incompletely understood mechanisms for innate signaling. For example, we have demonstrated that the nuclear damage-associated molecular patterns (DAMPs), HMGB1, and histone H3 undergo nuclear export and extracellular secretion in response to RSV; these DAMPs controlling mononuclear inflammation [38,41]. Informatics analysis indicated that RSV infected Scgb1a1-expressing bronchiolar cells selectively secrete 103 unique proteins and exosomal contents (Cluster 3 in Figure 1C).…”
Section: Nfκb Signaling In Bronchiolar Cells Generate Unique Innate Smentioning
confidence: 99%
“…Many DAMPs will therefore at this stage be expected to be present freely in the lungs and might contribute to the initiation of immune responses to the virus. Recently, RSV infection was shown to trigger the release of DAMPs such as high mobility group box 1 (HMGB1) 65 and S100A9 66 .…”
Section: Innate Immune Responses To Rsvmentioning
confidence: 99%
“…The HMGB1-mediated airway inflammation disease was characterized in the clinical and experimental asthma (35). In addition, HMGB1 from airway epithelial cells with respiratory syncytial virus infection primes epithelial cells and monocytes to inflammation stimuli in the airway (36). Multiple receptors were identified to be interacted with HMGB1, such as the receptor of advanced glycation end products (RAGE) or integrins, etc.…”
Section: Introductionmentioning
confidence: 99%